Introducing geographic information systems with ArcGIS : - Kennedy, Michael (John Wiley & Sons, 2006)
This book serves both as a general introduction to geographic information systems (GIS) and as a manual for a variety of functions of the ArcGIS Desktop applications. The exercises are full of useful, valuable hints and tricks that are not always found in other manuals and handbooks